MOREY, Miguel (2019). El hombre como argumento. Granada: Universidad de Granada. - Jiménez Villar, Beltrán (Daimon Revista Internacional de Filosofia, 2022)
Reseña del libro: MOREY, Miguel (2019). El hombre como argumento. Granada: Universidad de Granada.